2016
DOI: 10.4045/tidsskr.16.0011
|View full text |Cite
|
Sign up to set email alerts
|

Legers arbeidstid og tid til pasientarbeid i perioden 1994 – 2014

Abstract: Differences and changes in the amount of time spent by doctors on direct patient care are caused by both structural and cultural factors relating to the working situation, and not least by a considerable increase in the number of hospital doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 8 publications
0
36
3
7
Order By: Relevance
“…When women do the things men do not, their male counterparts are free to engage with activities that gain more merit and benefit their career and advancement in the medical hierarchy. Thus, it is not surprising that although women make up the majority of those entering medical classes, they remain under‐represented at higher levels of professorial rank, in leadership positions and in surgical specialties …”
Section: Louise: Gender and Who Gets To Be A Heromentioning
confidence: 99%
See 2 more Smart Citations
“…When women do the things men do not, their male counterparts are free to engage with activities that gain more merit and benefit their career and advancement in the medical hierarchy. Thus, it is not surprising that although women make up the majority of those entering medical classes, they remain under‐represented at higher levels of professorial rank, in leadership positions and in surgical specialties …”
Section: Louise: Gender and Who Gets To Be A Heromentioning
confidence: 99%
“…Thus, it is not surprising that although women make up the majority of those entering medical classes, they remain under-represented at higher levels of professorial rank, in leadership positions and in surgical specialties. 13 Observed gender differences in task distribution and attainment represent a challenge to the myth of medical meritocracy: if merit in medicine was essentially obtainable to all who accept that they have to work hard and well, women would outrank men. Studies have shown that female doctors work harder and longer, 14 managing a wider spectrum of health problems.…”
Section: Lou Is E: G Ender and Who G E Ts To B E A Heromentioning
confidence: 99%
See 1 more Smart Citation
“…Sannsynligvis er det godt samsvar mellom selvrapporterte data og mer objektive observasjoner innen dette feltet (2). En større svakhet ved studien er at respondentene oppfatter begrepet «pasientarbeid» ulikt (1). Så lenge samme spørs-mål er gjentatt over tid er det likevel grunn til å stole på at de markante tendensene som er påvist i studien er reelle.…”
unclassified
“…Det er betimelig å spørre: Har leger i dag tilstrekkelig praktisk og merkantil støtte til å kunne få brukt sin kompetanse på en effektiv måte? De siste 20 år er det blitt en dobling av antall leger i sykehus (1). Er det hensiktsmessig å fortsette denne utviklingen?…”
unclassified